The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/jgm-10-2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

International mobility and well-being of public sector expatriates

Abstract: Purpose The purpose of this paper is to examine the health-related well-being of public sector expatriates paying particular attention to the family situation. Design/methodology/approach A cross-sectional survey was conducted among the entire staff of the German Foreign Service (GFS), resulting in a response rate of 35.5 percent (analytical sample n=1,390). Partnership status, childlessness, and experiences of partnership break-ups were analyzed by gender and by age. Using OLS regression, the authors examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 74 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…Nevertheless, a number of pioneering studies on German emigrants have already been conducted and gathered valuable information. Their strategies to reach the target population, however, are often very complex and resource intensive (Ette et al, 2020), presuppose access to specific infrastructures or governmental institutions (Schupp et al, 2008;Waibel et al, 2018) respectively the assistance of private sector actors that could function as multiplicators (Pfeiffer & Heimer, 2007). These approaches are often successful in recruiting German emigrants who have left the country only quite recently and live in European countries, the United States of America, and Canada.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, a number of pioneering studies on German emigrants have already been conducted and gathered valuable information. Their strategies to reach the target population, however, are often very complex and resource intensive (Ette et al, 2020), presuppose access to specific infrastructures or governmental institutions (Schupp et al, 2008;Waibel et al, 2018) respectively the assistance of private sector actors that could function as multiplicators (Pfeiffer & Heimer, 2007). These approaches are often successful in recruiting German emigrants who have left the country only quite recently and live in European countries, the United States of America, and Canada.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, McNulty et al (2017) called for more research on overlooked occupational groups such as diplomats for a better understanding of the differences between business and governmental expatriation (e.g. Waibel et al , 2018). Our study, thus, contributes to the severely under-researched form of expatriation, namely diplomatic assignments, which are among the oldest types of expatriate profession (Fliege et al , 2016; Groeneveld, 2008; Davoine et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, this is exemplified by the positive association we found between RL and affective wellbeing at work. Extant expatriation research frequently tends to associate well-being with family and personal life (e.g., Mäkelä et al, 2017;Waibel et al, 2018) rather than with work-related leadership. Thus, RL may be viewed as a leadership approach that potentially reconciles various domains of social support.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lazarova, Westman, and Shaffer (2010) associated adjusted expatriates with an overall sense of well-being, while Shaffer et al (2012) classified subjective well-being as an intrinsic career outcome. Some expatriation research incorporates well-being in terms of family and personal life aspects (e.g., Mäkelä et al 2017;Waibel, Aevermann, & Rueger, 2018). For instance, Lämsä et al (2017) argue that parent companies should see travelling families as stakeholders, and that they need to develop and apply a holistic well-being orientation to show stakeholder responsibility.…”
Section: Affective Well-being At Workmentioning
confidence: 99%